1996
DOI: 10.1007/bf00141280
|View full text |Cite
|
Sign up to set email alerts
|

Is a signature of socio-economic impact written on the climate?

Abstract: Surging population associated with large-scale colonization, tropical deforestation, and industrialization in parts of Asia that constitute over 60% of the global population may lead to changes in the climate of that region. Identifying such changes is of great importance to scientists and policy makers. Concerning this, an approach is made here to assess the chemical composition in the troposphere over the region that happens to be the globe's longest belt of largest population density (LBLPD) and to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
0
14
1
Order By: Relevance
“…A study by Jones et al (1990) 23 on urbanization and related temperature variation indicates that the impact of urbanization on the mean surface temperature would be no more than 0.05 1C per 100 years. This value appears to be too small when compared with the other studies (Fujibe, 1995;Hingane, 1996) 20, 22 using a similar technique. According to the study for Japan by Fujibe (1995) 20 a rising trend of 2-5 1C per 100 years in minimum temperature has been observed at several large cities in Japan.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…A study by Jones et al (1990) 23 on urbanization and related temperature variation indicates that the impact of urbanization on the mean surface temperature would be no more than 0.05 1C per 100 years. This value appears to be too small when compared with the other studies (Fujibe, 1995;Hingane, 1996) 20, 22 using a similar technique. According to the study for Japan by Fujibe (1995) 20 a rising trend of 2-5 1C per 100 years in minimum temperature has been observed at several large cities in Japan.…”
contrasting
confidence: 56%
“…According to the study for Japan by Fujibe (1995) 20 a rising trend of 2-5 1C per 100 years in minimum temperature has been observed at several large cities in Japan. While another study (Hingane, 1996) 22 estimates rising trends of 0.84 and 1.39 1C per 100 years in the mean surface temperature calculated for Mumbai and Kolkata, respectively. Another study (Wibig and G"owicki, 2002) 25 related to the variability of minimum and maximum temperature in Poland reveals that the strongest increase in minimum and maximum temperatures occurs in mid and late winter.…”
mentioning
confidence: 92%
“…Studies carried out by several investigators have shown that the trend and magnitude of warming over India/the Indian sub-continent over the last century is broadly consistent with the global trend and magnitude (Hingane, 1995;Pant & Kumar, 1997, Arora et al, 2005, Dash et al, 2007. Pant & Kumar (1997) analysed the seasonal and annual air temperatures from 1881-1997 and have shown that there has been an increasing trend of mean annual temperature, at the rate of 0.57 C per 100 years.…”
Section: Signatures Of Climate Change Over Indiamentioning
confidence: 56%
“…Examination of long-term variation in the annual mean temperature of highly industrial and densely populated cities like Mumbai has shown an increasing trend. In Mumbai, the annual mean temperature has increased by 0.84°C per 100 years (Hingane, 1995). These warming rates are much higher than the values reported for the country as a whole.…”
Section: Signatures Of Warmer Climate Over Indiamentioning
confidence: 66%